The Effect of Dividend Payout Ratio (DPR), Total Asset Turnover (TATO), and Return on Investment (ROI) on Firm Value of PT. Bukit Asam, Tbk from 2013 to 2022 - Ida Yusnita; Tiara Lilis Surya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to: 1. To determine the influence of DPR on the value of PT. Bukit Asam, Tbk in 2013 – 2022. 2. To determine the effect of TATO on the value of the company PT. Bukit Asam, Tbk in 2013 – 2022. 3. To determine the effect of ROI on the value of the company PT. Bukit Asam, Tbk in 2013 – 2022. 4. To determine the influence of DPR, TATO and ROI on the value of PT. Bukit Asam, Tbk in 2013 – 2022 simultaneously. 5. To find out the influence of DPR, TATO and ROI on the value of PT. Bukit Asam, Tbk in 2013 – 2022 simultaneously. The research methodology used is with qualitative descriptive and quantitative descriptive approaches. The results of the study are; 1. Dividend Payout Ratio (DPR) does not affect the value of the company at PT. Bukit Asam, Tbk in 2013 – 2022. 2. Total Asset Turnover (TATO) does not affect the value of the company at PT. Bukit Asam, Tbk in 2013 – 2022. 3. Return On Investment (ROI) affects the value of the company at PT. Bukit Asam, Tbk in 2013 – 2022. 4. Simultaneously DPR, TATO and ROI affect the value of the company at PT. Bukit Asam, Tbk in 2013 – 2022. 5. The amount of influence of DPR, TATO and ROI on company value at PT. Bukit Asam, Tbk in 2013 – 2022 is 87.7%.